1993
DOI: 10.1093/protein/6.7.717
|View full text |Cite
|
Sign up to set email alerts
|

The fuzzy-end elimination theorem: correctly implementing the side chain placement algorithm based on the dead-end elimination theorem

Abstract: Recently it has been shown that the dead-end elimination theorem is a powerful tool in the search for the global minimum energy conformation (GMEC) of a large collection of protein side chains given known backbone coordinates and a library of allowed side chain conformational states, also known as rotamers. A side chain placement algorithm based on this theorem iteratively applies this theorem to single as well as to pairs of rotamers leading to the identification of rotamers, single or pairs, that are incompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 0 publications
0
64
0
Order By: Relevance
“…It may be possible to simplify the combinatorial nature of the side chain problem and reduce it to pairwise (36,37,38) or to self-consistency (19) methods. However, such approaches cannot produce an accurate or close approximation to the ensemble of structures, the ''best population'' that may be crucial for the physical and biological characteristics of a protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be possible to simplify the combinatorial nature of the side chain problem and reduce it to pairwise (36,37,38) or to self-consistency (19) methods. However, such approaches cannot produce an accurate or close approximation to the ensemble of structures, the ''best population'' that may be crucial for the physical and biological characteristics of a protein.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on the identification of rotamers that are absolutely incompatible with the global minimum energy conformation, eliminating rotamers that cannot contribute to local energy minima of a certain or higher order. Conformations composing such rotamers can be qualified as dead ending (30,36,37). If enough rotamers can be eliminated by recursive applications, the global minimum can be found (38,39).…”
mentioning
confidence: 99%
“…A number of studies have been reported, which exploit rotamer libraries for homology modeling, 46,47 protein design, 48,49 and ligand docking. 25,26,28 The space of receptor conformations arising from all possible rotameric combinations is often too large to sample exhaustively, and, thus, optimization and clustering techniques have been invoked, including Monte Carlo approaches, 48,50 simulated annealing, 51 dead-end-elimination 52 and its refinements, 53,54 and branch-and-bound schemes. 49 In protein structure prediction or design, the main aim is often to identify the single lowest energy conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy-end elimination 4 and improved forms of the elimination criteria 5 extend the utility of the theorem to more difficult problems. De Maeyer et al 6 have demonstrated that the calculation speed can be increased by simultaneously implementing an energy threshold and a more detailed rotamer library.…”
Section: Introductionmentioning
confidence: 99%
“…Lasters and Desmet 4 have described how the calculation can be continued by finding pairs of rotamers, called doubles, that cannot coexist in the GMEC. The variation is Ž .…”
Section: Introductionmentioning
confidence: 99%